Does Corruption Hurt Employment Growth of Financially Constrained Firms More? - Amin, Mohammad (World Bank E-Library Archive, 2020)
Payments of bribes and the expenses incurred on rent-seeking activities impose a significant financial burden on private firms, which is compounded when they do not have enough funds of their own or find it costly to borrow externally. This paper hypothesizes that financial constraints magnify the harmful effects of corruption. It applies this idea to the impact of corruption on employment growth among private firms. Using firm-level survey data for 109 countries, the analysis finds that corruption has a much larger negative impact on employment growth for firms that are financially constrained compared with firms that are not financially constrained. For the baseline specification, a one standard deviation increase in the bribery rate brings about a decline in the annual growth rate of employment of financially constrained firms that is 2.3 percent greater than that for firms that are not financially constrained. This is a large difference given that the mean employment growth is about 5.1 percent. The results show that corruption "sands the wheel" at high levels of financial constraint and "greases the wheels" of an otherwise slow bureaucracy at low levels of financial constraint